Modern Principles of Treatment of Uncontrolled Hypertension - V. I. Podzolkov; A. I Tarzimanova; Z. O. Georgadze (Столичная издательская компания, 2019)
Despite the current possibilities of using different classes of antihypertensive drugs that effectively reduce blood pressure and significantly improve the long-term prognosis of patients, the problem of uncontrolled arterial hypertension has not lost its importance and its solution in a particular clinical situation often remains very difficult. The term "uncontrolled arterial hypertension" can be used in all cases where arterial pressure has not been achieved. The true prevalence of uncontrolled arterial hypertension has not been established, and its study is hampered primarily by the fact that not all patients initially receive antihypertensive therapy that meets generally accepted standards. Currently, the tactics of management of patients with uncontrolled hypertension involves the use of combinations of antihypertensive drugs. Rational combinations, according to the new recommendations for the diagnosis and treatment of arterial hypertension in 2018, remain a combination of blockers of the renin-angiotensin-aldosterone system - angiotensin-converting enzyme inhibitors or receptor blockers to angiotensin with a calcium antagonist or diuretic, preferably in one tablet. With the ineffectiveness of dual therapy needs to be assigned to a third antihypertensive drug. Among the most modern antihypertensive drugs can be considered a triple fixed combination of lisinopril, amlodipine and indapamide. All the components included in the composition of the drug, has proved its high efficiency and safety. Uncontrolled arterial hypertension remains one of the most urgent problems of modern cardiology. Many aspects of it are far from unambiguously interpreted solutions and standards. Until the end, the mechanisms of the formation of uncontrolled course of hypertension remain unexplored, which, in turn, leads to a restriction of the use of drug and non-drug methods in the treatment of this pathology. Rational choice of antihypertensive therapy regimens can significantly improve the quality of treatment of this category of patients.